2020
DOI: 10.3390/jof6020047
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Influence of Olorofim (F901318) on the Cell Morphology and Organization of Living Cells of Aspergillus fumigatus

Abstract: The first characterized antifungal in the orotomide class is olorofim. It targets the de novo pyrimidine biosynthesis pathway by inhibiting dihydroorotate dehydrogenase (DHODH). The pyrimidines uracil, thymine and cytosine are the building blocks of DNA and RNA; thus, inhibition of their synthesis is likely to have multiple effects, including affecting cell cycle regulation and protein synthesis. Additionally, uridine-5′-triphosphate (UTP) is required for the formation of uridine-diphosphate glucose (UDP-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(47 reference statements)
2
13
1
Order By: Relevance
“…UTP is also important for the formation of the DNA/RNA pyrimidine derivatives cytosine, thymine, and uracil, as well as cell cycle regulation. Following 24 h of olorofim exposure, mitosis within A. fumigatus was halted, which is consistent with cell cycle arrest, and this was postulated to be due to a decrease in cellular levels of pyrimidine, leading to an inability to fully replicate DNA [ 28 ]. In addition to de novo synthesis, fungi are also able to acquire pyrimidine by scavenging from the environment.…”
Section: Mechanism Of Actionmentioning
confidence: 78%
See 3 more Smart Citations
“…UTP is also important for the formation of the DNA/RNA pyrimidine derivatives cytosine, thymine, and uracil, as well as cell cycle regulation. Following 24 h of olorofim exposure, mitosis within A. fumigatus was halted, which is consistent with cell cycle arrest, and this was postulated to be due to a decrease in cellular levels of pyrimidine, leading to an inability to fully replicate DNA [ 28 ]. In addition to de novo synthesis, fungi are also able to acquire pyrimidine by scavenging from the environment.…”
Section: Mechanism Of Actionmentioning
confidence: 78%
“…Thus, inhibition of pyrimidine synthesis by olorofim may affect the fungal cell wall and result in cell lysis [ 27 ]. An in vitro study reported that exposure of A. fumigatus hyphae to olorofim (0.1 μg/mL for 24 h) led to significant reductions in 1,3-β- d -glucan at the hyphal tips and at the periphery of the mycelium [ 28 ]. Interestingly, chitin content was significantly increased, which may be due to a compensatory mechanism that is known to occur with reduced 1,3-β- d -glucan levels following echinocandin exposure in different fungal species [ 29 , 30 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DHODH inhibitors exhibited efficacy against virus, including respiratory syncytial virus [ 109 ], rotavirus [ 110 ], foot-and-mouth disease virus infection [ 111 ], flavivirus which contains dengue virus, Zika virus, and Japanese encephalitis virus [ 112 ], and notably, against RNA viruses including newly emerged coronavirus SARS-CoV-2 [ 113 ]. DHODH inhibitors are also found to be effective against oomycete phytophthora infestans [ 114 ], schistosomiasis [ 115 , 116 ], invasive fungal infections [ 117 ], eumycetoma [ 118 ], and malaria [ 119 122 ].…”
Section: Dhodh and Non-neoplastic Diseasesmentioning
confidence: 99%